FrodoKEM based on multicore implementation: enhancing performance and memory efficiency in IoT applications - Amorim, Marcos V. C.; Lagrota, Vinícius; Filomeno, Mateus de L.; Ribeiro, Moisés V. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2025: Anais do XXV Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg.2025.6577, 2025)
This paper presents a multicore implementation of FrodoKEM, a post-quantum cryptographic scheme, targeting near real-time Internet of Things (IoT) applications. By combining tiled matrix multiplication and data parallelism, we enable FrodoKEM to efficiently operate under the memory and performance constraints of multicore microcontrollers. Implemented on the ESP32-S3, the single-core version demonstrates feasibility through memory optimization, while the dual-core version achieves a 44.5% reduction in execution time, meeting the latency requirements of IoT systems.